Legal Protection of The Fulfillment of The Right To Public Health Through The Establishment of Regional Regulations For Smoke-Free Areas - Galih Pratisto, Andito; Sabela, Adine; Fikriyansyah, Arisy; Dimyati, Agus; Sutrisno, Anom (Green Publisher Indonesia, 2024)
Based on the results of research in Majalengka Regency, it is very clear that the community wants a clean and healthy environment without exposure to cigarette smoke. Therefore, the Regional Government of Majalengka Regency needs to do to create a healthy and clean environment, so this needs to be a step to secure cigarettes for the health of both active and passive smokers through the establishment of a Smoke-Free Zone (KTR). Based on the above background, the purpose of this writing is as follows: a) To be able to find out what is the cause of the lack of a Regional Regulation on Non-Smoking Areas (KTR) in Majalengka Regency. b) To be able to find out what are the implications of the establishment of the Regional Regulation of Non-Smoking Areas (KTR) on the protection of the right to health in Majalengka Regency. The research method used is sociological juridical, which is legal research by looking at law as human behavior in society and then studied and reviewed based on relevant laws and regulations as a reference to solve problems. From a health perspective, cigarettes are the cause of death and pain that cause human misery and a decrease in quality of life and are contrary to Indonesia's human development. From a social and economic point of view, bad behavior of cigarette consumption violates human rights and is a means of impoverishing people. Based on the legal aspect, cigarettes are addictive substances which need to be regulated for the security of both production, distribution and use.